2021
DOI: 10.1007/s43546-021-00156-4
|View full text |Cite
|
Sign up to set email alerts
|

Do fluctuations in exchange rate hinder non-oil export? An analysis of agriculture and manufacturing in Nigeria

Abstract: This study examines the effect of exchange rate fluctuation on non-oil export by focusing on both manufactured exports and agriculture exports in Nigeria between 1970 and 2019. The study employs the vector error correction framework, the impulse response and variance decomposition analyses to analyse data on agriculture exports, manufacturing exports, exchange rate, interest rate, and inflation rate. Findings suggest that long run relationship exists among the variables. The vector error correction analysis re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 37 publications
(37 reference statements)
0
1
0
Order By: Relevance
“…Also, import substitution can improve the manufacturing sector, as seen by the positive correlation between the manufacturing sector and import penetration (Amali and Ajayi 2022). Previously, Mesagan et al (2021) posited that import substitution strategies have been observed to have a detrimental effect on the manufacturing sector in the near term. The inverse correlation between domestic cotton production and the output of the textile industry demonstrates this.…”
Section: Impacts Of Trade Policy On the Nigerian Manufacturing Sectormentioning
confidence: 99%
“…Also, import substitution can improve the manufacturing sector, as seen by the positive correlation between the manufacturing sector and import penetration (Amali and Ajayi 2022). Previously, Mesagan et al (2021) posited that import substitution strategies have been observed to have a detrimental effect on the manufacturing sector in the near term. The inverse correlation between domestic cotton production and the output of the textile industry demonstrates this.…”
Section: Impacts Of Trade Policy On the Nigerian Manufacturing Sectormentioning
confidence: 99%